Research of stress distribution in the cross-section of a bimetallic perforated plate perpendicularly loaded with concentrated force - Mateusz Konieczny; Henryk Achtelik; Grzegorz Gasiak (Fracture and Structural Integrity)
The paper presents the stress distribution along the plate thickness in a bimetallic steel – titanium circular, axially symmetrical perforated plate produced in the technological process of explosion welding. The steel layer is the layer that transfers the load in the plate, while the titanium layer is used to improve the properties of the plate, e.g. corrosion resistance, thermal transmittance, etc. in the plate. Two cases of fastening were considered, i.e. a freely supported and fixed plate. Such plates are used in various engineering structures, e.g. simply supported plates can be used in loose material screens, while plates are fixed in heat exchangers. The load was assumed as a concentrated force applied perpendicularly to the plate surface. The results obtained numerically using the finite element method were compared with the results calculated according to the analytical equations. It has been shown that the difference in the results of equivalent von Mises stress calculations does not exceed 13%. The research results presented in the paper can be used by engineers to design bimetallic perforated plates perpendicularly loaded to their surface.